Ascribed Rites of Passage among the Tharu Communities of Western Nepal - Chaudhary, Nathuram (KMC Journal, 2026)
This research aims to explore intercultural influences effect on the rites of passage in the Tharu communities of western Nepal. The study highlights on the complex relationship between traditional practices and contemporary changes on the rites of passage. Based on the ethnographic design, data were collected through Baatchit (conversational interviews) with eight social elites, comprising four elders aged over 70 and four Tharu teachers from higher education, as well as field observations with self-reflection. By applying modernization theory and Bhabha’s hybridization theory, the data were analyzed and interpreted through thematic as well as narrative analysis techniques centered on the rites of passage related to birth, marriage, and death. The findings of the study focused on a strong commitment to preserve cultural heritage, even within shifting lifestyles. However, the formal education of Nepal, the western social media shifting profession play a crucial role in influencing local practices, resulting in a hybridization of traditions. The study highlights the necessity of adapting traditional rites by incorporating modern elements to ensure their relevance for future generations.